Domínguez Serrano, Judith y Joaquín Flores Ramírez (2016), Derecho humano al agua y al saneamiento, Jiutepec, Mor., Instituto Mexicano de Tecnología del Agua / El Colegio de México, A.C. - Saldívar, Américo (Estudios Demográficos y Urbanos, 2017)
Domínguez Serrano, Judith y Joaquín Flores Ramírez (2016), Derecho humano al agua y al saneamiento, Jiutepec, Mor., Instituto Mexicano de Tecnología del Agua. El Colegio de México, A.C.